FDI, Trade Costs and Regional Asymmetries - Julia Darby; Ben Ferrett; Ian Wooton (Center for Economic Studies and ifo Institute (CESifo), 2013)
We set up a trade model where three countries compete for an exogenous number of firms. Our innovation lies in the geography of the model. Of the three countries, one is the hub through which all trade takes place. First, we establish the natural geography of the region, which is given by the equilibrium distribution of industrial activity in the absence of taxes or subsidies. We then examine the implications for corporate taxes when the countries compete with each other to attract firms. We find that, even when all countries are the same size, the centrality of the hub gives it an advantage in tax setting, such that its equilibrium tax can be larger than that of the spokes and yet it still attracts a disproportionate share of industry. Thus geographic advantage in tax competition has a second dimension, centrality in addition to size.
Keywords: F15; F23; H25; H73; 330; corporate taxes; devolution; trade costs